Evaluation of effectiveness of extracorporeal shock wave lithotripsy (ESWL) on the basis of stone density as measured by computed tomography (CT) in patients with renal stone (Bangladesh Medical Journal, 2016)
Renal stone or urolithiasis is the third most common disease of the urinary tract. ESWL has become the preferred treatment for renal calculi of